2014
DOI: 10.1021/jp505456q
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Voltammetric Behavior of Different Forms of Vitamin A in Aprotic Organic Solvents

Abstract: Six of the major vitamers and provitamins comprising vitamin A (β-carotene, retinoic acid, retinol, retinyl palmitate, retinyl acetate, and retinal) were examined using voltammetric and controlled potential electrolysis techniques in the aprotic organic solvents acetonitrile and dichloromethane at glassy carbon and platinum electrodes. All of the compounds underwent oxidation and reduction processes and displayed a number of similarities and differences in terms of the number of redox processes and chemical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…121 Retinal oxidation, shown in Figure 23 at (Figure 19 31 ). Reduction of β-carotene in dichloromethane, also shown in Figure 19, 31 has a peak potential at −2.15 V vs Fc|Fc + (−1.43 vs NHE) and the reaction is chemically irreversible.…”
mentioning
confidence: 99%
“…121 Retinal oxidation, shown in Figure 23 at (Figure 19 31 ). Reduction of β-carotene in dichloromethane, also shown in Figure 19, 31 has a peak potential at −2.15 V vs Fc|Fc + (−1.43 vs NHE) and the reaction is chemically irreversible.…”
mentioning
confidence: 99%
“…Nevertheless, it is necessary to state that authors proposed this reaction mechanism of retinol electrochemical oxidation based on the observation of only one oxidation peak at +0.79 V ( 13 ). Later, the study of electrochemical behaviour of several retinoids in CH 2 Cl 2 containing 0.2 M Bu 4 NPF 6 using cyclic voltammetry (CV) at GCE confirmed that retinal, retinoic acid, retinyl palmitate and retinyl acetate are oxidized in similar manner as retinol ( 27 ). Hence, oxidation of retinol to retinal is unlikely because the above-mentioned retinoids do not contain free hydroxyl group ( 27 ).…”
Section: Resultsmentioning
confidence: 90%
“…Later, the study of electrochemical behaviour of several retinoids in CH 2 Cl 2 containing 0.2 M Bu 4 NPF 6 using cyclic voltammetry (CV) at GCE confirmed that retinal, retinoic acid, retinyl palmitate and retinyl acetate are oxidized in similar manner as retinol ( 27 ). Hence, oxidation of retinol to retinal is unlikely because the above-mentioned retinoids do not contain free hydroxyl group ( 27 ). Meanwhile, Polish scientists studied electrochemical oxidation of retinyl propionate at Pt electrode in MeCN containing 0.1 M Bu 4 NClO 4 ( 28 ).…”
Section: Resultsmentioning
confidence: 90%
“…Despite that electrochemical behaviour of ELVs had been already the point of interest in several studies [4, 5], it was important to confirm initial assumptions; especially, if acetone has some effect on the anodic oxidation of both targeted compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, ELVs represent electrochemically active organic compounds which can be anodically oxidized at platinum and carbon‐based electrodes in glacial acetic acid or in acetonitrile containing perchlorate salt as the supporting electrolyte. Previous studies focused on electrochemical behaviour of the esters derived from all‐ trans ‐retinol suggest that cyclohexene ring (C3) probably represents the most energetically advantageous position for anodic oxidation [4, 5]. The α‐tocopheryl acetate (α‐TOAc) undergoes one‐electron oxidation resulting in radical cation (α‐TOAc +. )…”
Section: Introductionmentioning
confidence: 99%